The Cardiovascular effects of air pollution - Niekurzak, Rafał; Targońska, Marta; Targoński, Oskar; Buczek, Agnieszka; Ptasiński, Aleksander; Suława, Adrian; Basiak, Aneta; Furgalska, Julia; Fedorowicz, Sebastian (Quality in Sport, 2024)
Introduction and Purpose: Most cardiovascular problems are related to hypertension. Arterial hypertension is a persistent increase in blood pressure of 140/90 mm Hg or more. Hypertension usually does not cause symptoms for many years and if the blood pressure value is not regularly monitored, it is detected when complications occur in various organs (e.g. heart, kidneys, brain). The aim of the study was to determine the impact of air pollution on Cardiovascular effects. The article was based on the PubMed database. State of Knowledge: There are many factors that negatively affect the cardiovascular system (smoking, poor diet, sedentary lifestyle). Most of them can be corrected individually. Air pollution is such an example. Studies have been performed in many polluted cities around the world to investigate the relationship between air pollution and cardiovascular disease. Researchers found this to have a negative impact. Summary: This review describes what air pollution is in terms of particle size and their origin. Even though these particles enter the body through the respiratory tract, they can do just as much damage to the cardiovascular system and, based on some studies, even greater damage. At the end of the article, the focus is on personal and collective protection against air pollution.